A nuvem rosa : ensaio sobre personagens e roteiristas aprisionados - Gerbase, Iuli (2017)
This dissertation consists of two volumes. Volume I, which may be read first, presents the fourth version of the screenplay for the feature film The Pink Cloud. Volume II contains a theoretical reflection about the creative process of writing this script, from the initial idea to rewriting. Issues such as research for ficctional references, character development, creation of the outline, external constraints and the choice of endings are addressed.